2010
DOI: 10.1021/jp9104294
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Ultraviolet Photoluminescence of Tin Oxide Nanowires

Abstract: Photoluminescence (PL) properties of tin oxide (SnO 2 ) nanowires are studied in detail using high spectral resolution spectroscopy in a temperature range of 10-300 K. The nanowires have an average diameter of 86 nm. The high quality of the nanowires enables the observation of rich fine structures in the ultraviolet PL spectra at low temperatures. By carefully analyzing the temperature and excitation power dependent spectra, the following emissions are identified: recombination of donor-acceptor pairs, exciton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…The absorption tail evidences the formation of a phase with E g~3 .6 eV consistent with SnO 2 nanoprecipitation. The PL spectrum excited at 4.1 eV shows two distinct contributions, both in the UV spectral region, due to radiative recombination of SnO 2 -free excitons at ~3.6 eV (FX, cyan band) and to radiative decay of excitons in donor-acceptor sites 33,50 at ~3.3 eV (pink band). Importantly, in this excitation condition, no emission from Snrelated oxygen deficiency centres (ODCs) 49 or SnO 2 defects in the visible spectral region is observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption tail evidences the formation of a phase with E g~3 .6 eV consistent with SnO 2 nanoprecipitation. The PL spectrum excited at 4.1 eV shows two distinct contributions, both in the UV spectral region, due to radiative recombination of SnO 2 -free excitons at ~3.6 eV (FX, cyan band) and to radiative decay of excitons in donor-acceptor sites 33,50 at ~3.3 eV (pink band). Importantly, in this excitation condition, no emission from Snrelated oxygen deficiency centres (ODCs) 49 or SnO 2 defects in the visible spectral region is observed.…”
Section: Resultsmentioning
confidence: 99%
“…49) and the superposition of several contributions recently attributed to exciton bound to neutral donor (D 0 X) and donor-acceptor pair (DAP) recombinations 33,50 with a total FWHM of 0.13 eV. In regard to SnO 2 in lowdimensional systems, the strong quantum confinement causes the E g to shift towards higher energies and enables free-exciton decay (FX) 32,36 at 3.5-4 eV with a FWHM of 0.53 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Here, the UV emission band at 361 nm is attributed to band edge recombination of the photogenerated carriers, which may be originated from the conduction band to acceptors and neutral-donar-bound excitons. [47][48][49] For the SnO 2 nanowires sample, the above XPS result reveals that oxygen vacancies are formed on the SnO 2 nanowire surface. The oxygen vacancies can form acceptor level which results in a blue emission band at 445 nm.…”
Section: Resultsmentioning
confidence: 91%
“…Up to now, the photoluminescence mechanism of SnO 2 is still not clear. [43][44][45][46][47][48][49] It is believed that the surface oxygen vacancies defect states can induce direct gap transitions and generate possible photoluminescence. [43][44][45] Recently, Li et al found that that the SnO 2 nanostructures can break the dipole-forbidden rule and realize UV luminescence.…”
Section: Resultsmentioning
confidence: 99%